Rancang Bangun Sistem Penjualan Furniture Menggunakan Metode Exponential Smoothing - Ambarwati Ambarwati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Furniture Agung is an MSME engaged in furniture located in the district of Semarang. MSMEs are still conducting data collection, processing and transactions that are carried out manually. This process becomes ineffective and inefficient because errors can occur in recording and data can be lost. This research aims to design an information system for furniture sales and sales forecasting using the exponential smoothing method in September 2020 to May 2021. Based on the results of sales analysis testing using the exponential smoothing method using alpha 0.2 in May 2021, the calculation of forecasting demand for furniture products as many as 41 pieces. The results of calculations using mean square error (MSE) alpha 0.2 to predict the error rate of furniture demand are: 69.22 = 69. This system research uses a codeigniter framework, and MySql as a database server. The design of the web-based system is expected to make it easier for MSMEs to conduct digital transactions and manage goods data so that data reports can be known easily, quickly, accurately, and data is stored safely